2012
DOI: 10.1120/jacmp.v13i2.3707
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effects of jaw tracking in step‐and‐shoot intensity‐modulated radiation therapy

Abstract: The purpose of this work was to determine the dosimetric benefit to normal tissues by tracking the multi‐leaf collimator (MLC) apertures with the photon jaws in step‐and‐shoot intensity‐modulated radiation therapy (IMRT) on the Varian 2100 platform. Radiation treatment plans for ten thoracic, three pediatric, and three head and neck cancer patients were converted to plans with the jaws tracking each segment's MLC apertures, and compared to the original plans in a commercial radiation treatment planning system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…Furthermore, Darby et al looked into risk of ischemic heart disease after breast radiation therapy and concluded that was an increasing magnitude of the risk of 7.4% per Gray with no apparent threshold below which there was no risk. Many of the previous studies evaluated RIHD using different imaging modalities to detect functional abnormalities, without correlation of the actual radiation treatment volume 41, 42, 43, 44, 45. Our results also show the same trend of higher radiation damage with increasing dose.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, Darby et al looked into risk of ischemic heart disease after breast radiation therapy and concluded that was an increasing magnitude of the risk of 7.4% per Gray with no apparent threshold below which there was no risk. Many of the previous studies evaluated RIHD using different imaging modalities to detect functional abnormalities, without correlation of the actual radiation treatment volume 41, 42, 43, 44, 45. Our results also show the same trend of higher radiation damage with increasing dose.…”
Section: Discussionsupporting
confidence: 78%
“…A few investigators have reported the dosimetric advantages of jaw tracking techniques for IMRT and VMAT planning . For instance, Joy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the advantages of JT‐IMRT/VMAT plans with flattened beams have been studied previously, the dosimetric impact of JT technique with FFF beam in the treatment of lung SBRT patients, along with the treatment delivery complexity due to the use of JT with MLC motion has not yet been reported. The goals of this project were to quantify the dosimetric differences of JT technique for FFF beam in the SBRT treatment of multifocal lung lesions and to investigate the JT delivery complexity with MLC movements.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize nontarget dose, jaws and MLC leaves should be closed to the extent possible. For a tertiary MLC, Joy et al 314 considered tracking the MLC opening with the jaws for each segment of an IMRT delivery, thereby reducing leaf leakage. This approach reduced the V5 and V20 volumes of organs at risk near the edge of the treatment field by around 2% (absolute volume).…”
Section: G Jaw Trackingmentioning
confidence: 99%